Investigating the Emotional Trajectory of Ph.D. Students via Qualitative Research: Bridging the Gap between Expectations and Reality - Shuyang Zhang; Rose Manisah Binti Sulong; Norlizah Binti Che Hassan (Universitas Pendidikan Indonesia (UPI), 2024)
This study investigated the study motivation and psychological responses of pre-second-year Ph.D. students from a comprehensive university in Malaysia. To gain an understanding of the challenges faced by students, we conducted group interviews with 15 pre-second-year students: Malay, Chinese, and Malaysian Chinese. The interview transcripts were analyzed thematically using Atlas. The results revealed three significant challenges: The passion for pursuing a Ph.D. diminishes over time.; The stark contrast between self-expectations and the harshness of reality; The challenges of reality give birth to the hope for pursuing a Ph.D. The finding suggests some implications for educators and students regarding active learning.